Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1002/art.1780381002
|View full text |Cite
|
Sign up to set email alerts
|

Special article the economic cost and social and psychological impact of musculoskeletal conditions

Abstract: Objective. To provide an indication of the economic, social, and psychological impact of musculoskeletal conditions in the United States.Methods. Review of the literature combined with estimates of data concerning health care utilization and acute and chronic disability due to musculoskeletal conditions, from the 199&1992 National Health Interview Survey.Results. The cost of musculoskeletal conditions was $149.4 billion in 1992, of which 48% was due to direct medical care costs and the remainder was due to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
222
1
9

Year Published

1995
1995
2004
2004

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 417 publications
(238 citation statements)
references
References 41 publications
2
222
1
9
Order By: Relevance
“…In 1995, the National Arthritis Data Workgroup reported that both direct and indirect costs of all forms of musculoskeletal conditions, including AORC, for 1988 was 2.5% of the gross national product of the US (6). In the present study, however, we found that total medical expenditures for AORC alone in 1997 were equivalent to ϳ2.3% of the gross domestic product for that year (48), and would suggest that both the accounting methods used in the MEPS and the aging of the population may have contributed to the increase in the estimated impact of these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, the National Arthritis Data Workgroup reported that both direct and indirect costs of all forms of musculoskeletal conditions, including AORC, for 1988 was 2.5% of the gross national product of the US (6). In the present study, however, we found that total medical expenditures for AORC alone in 1997 were equivalent to ϳ2.3% of the gross domestic product for that year (48), and would suggest that both the accounting methods used in the MEPS and the aging of the population may have contributed to the increase in the estimated impact of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the growing importance of cost of illness studies in health policy, the literature concerning the cost of all forms of musculoskeletal conditions for the US as a whole (1)(2)(3)(4)(5)(6)(7)(8) and for other nations (9)(10)(11)(12)(13), as well as the cost of specific musculoskeletal conditions, including various forms of arthritis and other rheumatic conditions (AORC) , has been expanding rapidly.…”
mentioning
confidence: 99%
“…Otherwise, the condition is allocated to a generic category, such as "musculoskeletal disease." Yelin and Callahan (6) merged three years of HIS data to provide more stable estimates of the prevalence of work disability. They reported that about 57% of persons with a musculoskeletal condition were not working and that 64% of those with a code for RA were not working.…”
Section: Introductionmentioning
confidence: 99%
“…We first partitioned the MEPS-H data into the following condition groups on the basis of ICD-9 codes: persons with only musculoskeletal conditions (ICD-9 codes 274 and 710-738), persons with both musculoskeletal and nonmusculoskeletal chronic conditions, persons with 1 nonmusculoskeletal condition, persons with 2 or more nonmusculoskeletal chronic conditions, and persons with no chronic conditions. The definition of musculoskeletal conditions is based on the recommendation of the National Arthritis Data Task Force (7). Chronic conditions in general are defined by the protocol devised by Hoffman et al (43).…”
Section: Methodsmentioning
confidence: 99%
“…whole (1)(2)(3)(4)(5)(6)(7), as well as the cost of specific musculoskeletal conditions , has been expanding rapidly. In addition, there is growing literature on the impact of managed care on the health care utilization of persons with musculoskeletal conditions, with most of the studies indicating that persons receiving care in managed care plans do not systematically differ in their health care from those receiving it in the fee-for-service sector (36)(37)(38)(39)(40).…”
mentioning
confidence: 99%